1998
DOI: 10.1046/j.1471-4159.1998.71062642.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Vulnerability to 3‐Nitropropionic Acid in an Animal Model of Huntington's Disease

Abstract: There is substantial evidence for both metabolic dysfunction and oxidative damage in Huntington's disease (HO). In the present study, we used in vivo microdialysis to measure the conversion of 4-hydroxybenzoic acid to 3,4-dihydroxybenzoic acid (3,4-DHBA) as a measure of hydroxyl radical production in a transgenic mouse model of HO, as well as in littermate controls. The conversion of 4-hydroxybenzoic acid to 3,4-DHBA was unchanged in the striatum of transgenic HO mice at baseline. Following administration ofth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 13 publications
0
53
2
Order By: Relevance
“…One such naturally occurring plant toxin, 3-nitropropionic acid (3-NP), is an irreversible inhibitor of succinate dehydrogenase and both the Krebs cycle and complex II activity of the electron transport chain (19). 3-NP is associated with HD-like symptoms in both humans and animals and, as such, has been used as an experimental model for HD (20). We further hypothesized that mitochondria may be more susceptible to mitochondrial toxins in the presence of a dominant negative or mutant mitochondrial CREB.…”
Section: Resultsmentioning
confidence: 99%
“…One such naturally occurring plant toxin, 3-nitropropionic acid (3-NP), is an irreversible inhibitor of succinate dehydrogenase and both the Krebs cycle and complex II activity of the electron transport chain (19). 3-NP is associated with HD-like symptoms in both humans and animals and, as such, has been used as an experimental model for HD (20). We further hypothesized that mitochondria may be more susceptible to mitochondrial toxins in the presence of a dominant negative or mutant mitochondrial CREB.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several reports suggesting altered sensitivity of transgenic HD mice to malonate or 3-NP (41)(42)(43). Also, a previous study from our laboratory showed that striatal cells expressing mutant huntingtin were more sensitive than wildtype cells to 3-NP induced toxicity, but not to rotenone treatment (17).…”
Section: Fig 4-continuedmentioning
confidence: 92%
“…of six independent experiments. huntingtin-induced alterations in the mitochondrial ATP-sensitive K ϩ channel could explain the decreased ⌿m and calcium retention capacity reported in several HD models (13), as well as the altered sensitivity of transgenic HD mice to malonate or 3-NP (41)(42)(43). Our future studies will be directed toward examining this possibility.…”
Section: Fig 4-continuedmentioning
confidence: 97%
“…It has been shown previously that transgenic HD mice are resistant to excitotoxic lesions (Hansson et al, 1999(Hansson et al, , 2001aHickey and Morton, 2000;Petersen et al, 2001;MacGibbon et al, 2002), although this is age, strain, and excitotoxin dependent (Bogdanov et al, 1998;Hansson et al, 2001a;Petersen et al, 2002;Schauwecker, 2002;Zeron et al, 2002). QA has been used in various doses to induce lesions in mice [1 l of 8, 20, and 30 nmol (Zeron et al, 2002;Hansson et al, 2001b;Petersen et al, 2002, respectively], so, in the present study, a larger dose (40 nmol) was given to all animals in an attempt to induce a lesion in R6/2 mice.…”
Section: R6/2 Mice Are Resistant To Qa-induced Striatal Lesionsmentioning
confidence: 99%